(untitled) (Eurasian Scientific Herald, 2023)
The article discusses the most common causes of the development of perforation of the maxillary sinus and odontogenic perforated sinusitis in modern conditions. Perforation of the bottom of the cavity of the maxillary sinus is one of the most common complications that arise directly during tooth extraction surgery